(untitled) (Kronika Bydgoska, 2010)
This article devoted to the activity of Marian Kiersnowski (1873-1949) a designer of church interiors, fumiture and fumishings, and a pedagogue - is the first synthetic monograph about this artist. He was educated in St. Petersburg and at first worked in Russia. Later, he moved to Poland, and lived in, among others, Toruń and Bydgoszcz. In the years 1921-1922, he worked in the Luxurious Fumiture Factory of the American Association “Polamerica” in Toruń. Next, he started to work as a teacher in Bydgoszcz schools - State School of the Art Industry and State School of Industry, where he worked in the years 1922-1933. Finally, in 1933, he settled permanently in Kodeń on the Bug River. His life and work was connected with the Missionary Oblates of Mary Immaculate. On the monastery premises, he had St Joseph’s sculp- tural and carpenter’s workshop. He designed and madę a significant part of the fumishings of St Anna’s Basilica in Kodeń. Based on the preserved archival materials, a set of design drawings, old photographs, and facilities mostly still existing, an attempt at reconstructing the gradual shaping of the church decor has been presented - the church presently functioning in the awareness mainly as the Sanctuary of Our Lady of Kodeń.